ANALYSIS OF DECISION OF CENTRAL JAKARTA COURT NUMBER 757/Pdt.G/2022/PN Jkt.Pst (FROM PMH TO ABUSE OF POWER) - Ratu Faridatul Fauziyah (LPPM Universitas Ekasakti Padang, 2023)
On March 2, 2023, the Central Jakarta District Court decided to accept the PRIMA party's lawsuit, declared the PRIMA party the party that was harmed, ordered the defendant to pay a fine of five hundred billion, punished the defendant in this case, the KPU not carrying out the remaining stages of the KPU, and so on. On the one hand, this decision is considered to be in the wrong room, and the JAKPUS District Court judges exceeded their authority, especially regarding the election postponement clause. However, on the other hand, this decision was aimed at justice for the PRIMA party due to the KPU's negligence. Based on this, the research seeks to analyze more deeply and comprehensively whether the JAKPUS District Court decision was in the wrong chamber and the judge exceeded his authority or whether this decision was indeed in his room. This research is normative research with a normative juridical approach. The legal material used in this study is secondary legal material, namely in the form of a JAKPUS District Court decision number 757/Pdt.G/2022/PN.Jkt.Pst, laws and regulations, doctrine, expert opinions, and so on related to the theme of this research. In addition, no research specifically examines this decision. The results of this study indicate that the unlawful act referred to in this case is a legal act committed by a government agency/institution, which is the authority of the Administrative Court as outlined in PERMA Number 2 of 2019. In addition, the judge's actions in handling this case fall into the category of abuse of power for exceeding their authority and not implementing the written rules, in this case, PERMA Number 2 of 2019